Private post-secondary library websites and the ADA: compliancy and COVID-19 - Bielefield, Arlene; Liu, Yan Quan; Waimon, Victoria (Universal Access in the Information Society, 2023)
This study explores whether US post-secondary institutions (PPI) follow philosophies to foster inclusive communities, providing resources for those individuals with disabilities thrive socially, personally, and academically, while there have been no thorough studies conducted to determine web accessibility of the nation’s top-ranked PPI library webpages. Additionally, this study pioneers in comparison with the accessibility of PPI’s library homepages fighting COVID-19. The study evaluated the library homepages of the premium PPIs based on Money.com’s 2019 list of “The Best Colleges in America” via the WAVE web accessibility evaluation tool. The outcomes determined that most of the library homepages analyzed were littered with numerous errors, and the shift to online-based research in learning had no significant impact on the number of errors WAVE detected. The disconcerting findings of this study demonstrate the overall failure to recognize the importance of web accessibility or perhaps even the indifference toward accessibility on the part of the PPI community.
Keywords: ADA; Academic libraries; Accessibility; COVID-19; Disability; Overall failure; Philosophical aspects; Post-secondary institutions; Private colleges and universities; SCSU-student; Section 508; WAVE; WCAG; Web accessibility; Websites; dept.ils; peer-reviewed

Academic pursuits and involvement in decision-making: study on the formation of U.S. university think tanks - Lyu, Qing; Bielefield, Arlene; Liu, Yan Quan (Administrative Sciences, 2023)
This paper analyzes the concept of think tanks and concludes that think tanks have three basic characteristics. Firstly, they are based on academic research, relatively independent operation, and aim to serve scientific decision-making. Taking Ivy League think tanks as an example, this paper provides a preliminary discussion of ways for think tanks to maintain the scientific nature of their research, maintain the independence of their operations, and disseminate research results to enhance their influence. It covers institutional mission, research team construction, institutional governance, fundraising, achievements and activities, and alumni networks. This paper proposes a framework of university think tank generation paths associated with the essential characteristics of think tanks. The paper points out that, as a research consulting organization grown out of universities, university think tanks must maintain the scientific nature and independence of research while providing support and services for decision-making. Only in this way can they truly serve scientific and democratic decision-making, gain the trust of the public and have a real lasting influence.
Keywords: American university affiliated think tank; characteristics of think tank; decision-making; dept.ils; peer-reviewed; the ivy league university; think tank operation mechanism